PENGARUH SERVANT LEADERSHIP TERHADAP EMPLOYEE EMPOWERMENT, ORGANIZATIONAL CULTURE DAN COMPETITIVE ADVANTAGE PADA UNIVERSITAS DI SURABAYA - Hendri Kwistianus (Business Accounting Review, 2015)
This study aimed to know whether there was influence between the Servant Leadership to Employee Empowerment, Organizational Culture and Competitive Advantage. Servant Leadership variables were measured from five indicators, namely altruistic calling, emotional healing, wisdom, persuasive mapping, and organizational stewardship. Competitive Advantage variables were measured from five indicators: differentiation and quality of the products, cost of products, innovation, growth, and alliances. Employee Empowerment variables were measured from four indicators, namely competence, meaningful, self-determination, and impact. Organizational Culture variables were measured from four indicators, namely clan, adhocracy, market and hierarchy. The data were collected by distributing questionnaires. The unit of analysis was 10 to 15 lecturers each from six universities in Surabaya. The method of analysis used in testing the hypothesis was Structural Equation Modeling (SEM) by using Partial Least Square (PLS).This research proved that servant leadership had positive impact to Competitive Advantage, Employee’s Empowerment and Organizational Culture while Employee’s Empowerment had positive impact to Competitive Advantage, and Organizational Culture had positive impact to Competitive Advantage.